Bacterial Community Structure Associated with a Dimethylsulfoniopropionate-Producing North Atlantic Algal Bloom - González, José M. (American Society for Microbiology, 2000)
The bacteria associated with oceanic algal blooms are acknowledged to play important roles in carbon, nitrogen, and sulfur cycling, yet little information is available on their identities or phylogenetic affiliations. Three culture-independent methods were used to characterize bacteria from a dimethylsulfoniopropionate (DMSP)-producing algal bloom in the North Atlantic. Group-specific 16S rRNA-targeted oligonucleotides, 16S ribosomal DNA (rDNA) clone libraries, and terminal restriction fragment length polymorphism analysis all indicated that the marine Roseobacter lineage was numerically important in the heterotrophic bacterial community, averaging >20% of the 16S rDNA sampled. Two other groups of heterotrophic bacteria, the SAR86 and SAR11 clades, were also shown by the three 16S rRNA-based methods to be abundant in the bloom community. In surface waters, the Roseobacter, SAR86, and SAR11 lineages together accounted for over 50% of the bacterial rDNA and showed little spatial variability in abundance despite variations in the dominant algal species. Depth profiles indicated that Roseobacter phylotype abundance decreased with depth and was positively correlated with chlorophyll a, DMSP, and total organic sulfur (dimethyl sulfide plus DMSP plus dimethyl sulfoxide) concentrations. Based on these data and previous physiological studies of cultured Roseobacter strains, we hypothesize that this lineage plays a role in cycling organic sulfur compounds produced within the bloom. Three other abundant bacterial phylotypes (representing a cyanobacterium and two members of the α Proteobacteria) were primarily associated with chlorophyll-rich surface waters of the bloom (0 to 50 m), while two others (representing Cytophagales and δ Proteobacteria) were primarily found in deeper waters (200 to 500 m).